The negative effects of extracellular vesicles in the immune system - Wang, Yang; Li, Cuifang; Wu, Feifeng; Mao, Jueyi; Zhu, Junquan; Xie, Haotian; Zhou, Xin; Wen, Chuan; Tian, Jidong (Frontiers in Immunology, 2024)
Immunity is a critical self-defense mechanism of the human body, wherein immune cells and immune molecules play a crucial role. Extracellular vesicles (EVs), derived from immune cells or other cells, play a significant role in tumors, autoimmune diseases and other immune-related disorders by serving as carriers and facilitating intercellular communication through the transfer of cargoes. Numerous studies have revealed that EVs can exacerbate disease development by modulating immune responses. Therefore, this paper focuses on the effects of EVs on the number, activity and function of different types of immune cells and the release of immune molecules (such as cytokines, antigens, antibodies, etc) in various diseases, as well as the roles of EVs associated with different types of immune cells in various diseases. We aim to provide a comprehensive review of the negative effects that EVs play in the immune system to provide more ideas and strategies for the management of clinical immune diseases.